The Chicago Lead Knowledge Test-Malay Version: a cultural and linguistic adaptation for the Malaysian population - Mohd Shahrol AW,; Mohd Hasni Ja’afar,; Zaleha Md Isa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Knowledge about exposure to lead among children is still not good among parents in Malaysia. The purpose of this study was to translate the English version of the original Chicago Lead Knowledge Test (CLKT) into the Malay (local) language systematically and to suit the background culture and language of this country. The steps of systematic translation followed the International Society for Pharmacoeconomics and Outcome Research (ISPOR) standard which consists of preparation, forward translation, reconciliation, backward translation, backward translation review, harmonisation, cognitive debriefing, review of cognitive debriefing and finalisation, proofreading, and final report. The total number of items remained at 24, where one item was deleted, one item was revised, and one item was added into the instrument. All four themes; general knowledge, exposure, prevention and nutrition in this questionnaire were maintained. The response scale, answer scheme, and the scoring system remained the same. Most of the English items had direct translation to Malay language except for items 5, 7, 12, 20 and 22. The mean (+SD) and interquartile range (IQR) for total knowledge score was 9.50 + 2.45 marks and 5 marks, respectively. The lowest score was 4 marks and the highest score was 13 marks. This was be the first known study to utilise the systematic and standardised approaches in the cross-cultural translation and adaptation of the CLKT in Malaysia. The CLKT’s cultural and linguistic adaptation in Malaysia may contribute to other current research particularly on lead exposure among children.